Challenger and Propose Novel Methods and Techniques for Prevention, Prognosis, Diagnosis, Imaging, Screening, Treatment and Management of Lung Cancer - Alireza Heidari; Elena Locci; Silvia Raymond; Ricardo Gobato (Journal of Lung Cancer Epidemiology, 2022)
Using samples of small cell lung tumors, a research team led by biologist Dr. Raymond discovered two new ways to induce tumor cell death. By activating ferroptosis, one of two subtypes of tumor cells can be targeted: first, iron-dependent cell death due to oxidative stress, and second, oxidative stress. Therefore, cell death can also be induced in a different way. Both types of cell death must be caused by drugs at the same time to eliminate the majority of the tumor mass. It is currently in clinical trials for cancer treatment. Auranofin, which inhibits the production of protective antioxidants in cancer cells, has been used to treat rheumatoid arthritis for decades. Future clinical trials using this combination therapy will determine the extent to which this targeted treatment option improves the prognosis of small cell lung cancer patients. It is currently in clinical trials for cancer treatment. Lung cancer is the leading cause of cancer death in the United States. Despite evidence of molecular abnormalities in biological specimens, progress in this disease is hampered by the lack of diagnostic markers useful for clinical practice. The majority of patients with lung cancer are still diagnosed at an advanced stage, when prognosis is poor. This article reviews new strategies being studied for the early detection of lung cancer. These strategies involve new methods of imaging (including low-dose computed tomography CT scanning), DNA analysis, and proteomic-based techniques. These strategies have not only improved our understanding of lung cancer but show promise in offering better survival to patients with this deadly disease. Of paramount importance in the search for methods of early detection is the need for the identification of the ideal population to screen, a multidisciplinary approach, and validation of promising techniques.
Keywords: Lung Cancer